Urbanization and childhood asthma - Pham, Teresia T.; Akinbolagbe, Yeside; Nguyen, Thinh H.; Phipatanakul, Wanda (Pediatric allergy and immunology, 2025)
Childhood asthma is one of the major public health concerns, and urbanization as well as worsening environmental factors are contributing to its increasing prevalence. Outdoor pollutants, such as PM2.5, ozone, and traffic‐related air pollution or TRAP, play significant roles in exacerbating asthmatic symptoms in children as well as reducing their lung function. Climate change can further compound these effects with changing pollen patterns that increase exposure to allergens in certain geographical areas. Moreover, indoor environments in urban areas also expose children to pollutants such as nitrogen dioxide, particulate matter, and aeroallergens like cockroach or mouse allergens. Socioeconomic disparities can further amplify these effects, with children in minority or low‐income households disproportionately burdened by asthma morbidity. Green infrastructure and technological innovations can offer mitigation opportunities for negative effects of urbanization but require careful implementation to address multifactorial contributors to childhood asthma. Our review highlights the need for integrated strategies regarding environmental regulation, urban planning, and targeted interventions to reduce asthma burden in the urban pediatric population.